Choosing R&D or advertising for competing firms in uncertain market - Bo Xie; Xianjia Wang (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: R&D and advertising have become important means to enhance the competitiveness of firms' products. Design an appropriate model to help the firm to make the right choice is value in supply chain.Design/methodology/approach: In considering that whether the market is completely covered or not, we build the strategy selection model for R&D and advertising for two competing firms and solve the optimal strategy. Findings and Originality/value: The research results show that when a firm does not take any measures to enhance competitiveness, another firm will neither. However when one takes measures to improve the competitiveness, another will do so, also. When two firms must choose one measure to improve the competitiveness, either in full-covered market or not full-covered market, the two firms will not choose to do advertising in step, even if the firms do not have to pay additional cost in advertising. Originality/value: In the game model, the firm could compare the own profit in different strategies. According to the above model, the firm choose the right strategy to make the profit maximize in a vertically differentiated market. And when the firm make the choice, it must think about other primary elements such as market.
Keywords: 650; R&D; advertising; production competition; Hotelling model